2018
DOI: 10.3168/jds.2017-13857
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal effects of ruminal propionic acid infusion on feeding behavior of Holstein cows in the postpartum period

Abstract: The objective of this study was to determine the temporal effects of intraruminal infusion of propionic acid at the initiation of meals on feeding behavior of cows in the postpartum period. Propionic acid derived from ruminal fermentation can reduce energy intake of dairy cows. The suppression of appetite by propionic acid is likely caused by a signal related to the hepatic oxidation of fuels. Greater propionate flux to the liver is expected to result in faster oxidation of acetyl coenzyme A, which can stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
(35 reference statements)
3
19
0
Order By: Relevance
“…Therefore, hepatic oxidation might have been slower for FST compared with SLW because acetyl CoA concentration was not reduced by FST during the time frame of meals. That would explain how FST allowed for greater meal size in our previous experiment (Maldini and Allen, 2018). Consistent with this, Piantoni et al (2015) showed a positive relationship between the extent of reduction in plasma NEFA concentration and DMI during the first 4 h after feeding for cows in the PP period and that the reduction in plasma NEFA concentration and the reduction in hepatic acetyl CoA concentration were linearly related.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Therefore, hepatic oxidation might have been slower for FST compared with SLW because acetyl CoA concentration was not reduced by FST during the time frame of meals. That would explain how FST allowed for greater meal size in our previous experiment (Maldini and Allen, 2018). Consistent with this, Piantoni et al (2015) showed a positive relationship between the extent of reduction in plasma NEFA concentration and DMI during the first 4 h after feeding for cows in the PP period and that the reduction in plasma NEFA concentration and the reduction in hepatic acetyl CoA concentration were linearly related.…”
Section: Discussionsupporting
confidence: 83%
“…In a previous experiment, we observed an increase in meal size and extended time between meals by FST, reducing meal frequency of cows in the PP period (Maldini and Allen, 2018), and we hypothesized that FST saturated the pathway for propionate metabolism resulting in a lower first-pass extraction by the liver compared with SLW. However, the results of this experiment do not support our hypothesis.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The animals’ appetite, feeding behaviour, and gastrointestinal motility (among other traits) are thought to be regulated by several mechanisms, including a communication between the rumen microbiome and the brain, through the gut–liver–brain axis (vagus nerve). This communication has been proposed to be mediated by multiple mechanisms, such as insulin/glucagon homeostasis, oxidation of acetyl coenzyme A, and release of VFA by the rumen microbiota (like propionate, associated with hypophagic behavior in ruminants, or butyrate and acetate, associated with motility of the gastrointestinal tract in monogastric animals; Sakata and Tamate, 1979; Cherbut, 2003; Oba and Allen, 2003; Arora et al, 2011; Maldini and Allen, 2018). Given the predictability of performance traits using relative abundances of rumen microbial genes observed in the present research (particularly that of DFI) and the high impact of the rumen microbiome on feed intake regulation (as discussed in the literature), we hypothesize that rumen microbial genes are closely involved in the metabolic pathways that regulate feed intake.…”
Section: Discussionmentioning
confidence: 99%